Barriers faced by Ugandan university students in seeking medical care and sexual health counselling: a cross-sectional study - Boltena Andualem Tadesse; Khan Farhad Ali; Asamoah Benedict O; Agardh Anette (BMC, 2012)
Abstract Background Meeting the medical and sexual health care needs of young people is crucial for sustainable development. In Uganda, youth are faced with a number of challenges related to accessing medical care and sexual health counselling services. This study sought to investigate the barriers faced by Ugandan university students in seeking medical care and sexual health counselling. Methods This study is part of a cross-sectional survey conducted in 2005 among 980 students at Mbarara University of Science and Technology. Data was collected by means of a self-administered 11-page questionnaire. The barriers encountered by respondents in seeking medical care and sexual health counselling were classified into three categories reflecting the acceptability, accessibility, or availability of services. Results Two out of five students reported unmet medical care needs, and one out of five reported unmet sexual health counselling needs. Acceptability of services was the main barrier faced by students for seeking medical care (70.4%) as well as for student in need of sexual health counselling (72.2%), regardless of age, gender, self-rated health, and rural/peri-urban or urban residence status. However, barriers differed within the various strata. There was a significant difference (p-value 0.01) in barriers faced by students originally from rural versus peri-urban/urban areas in seeking medical care (acceptability: 64.8%/74.5%, accessibility: 22.0% /12.6%, availability 13.2%/12.9%, respectively). Students who reported poor self-rated health encountered barriers in seeking both medical care and sexual health counselling that were significantly different from their other counterparts (p-value 0.001 and 0.007 respectively). Conclusions Barriers faced by students in seeking medical and sexual health care should be reduced by interventions aimed at boosting confidence in health care services, encouraging young people to seek early treatment, and increasing awareness of where they can turn for services. The availability of medical services should be increased and waiting times and cost reduced for vulnerable groups.